PEMENUHAN KEBUTUHAN SEKOLAH MITRA MELALUI PROGRAM MBKM (STUDI PELAKSANAAN PROGRAM KAMPUS MENGAJAR DI KABUPATEN GOWA) - Irmawati, Irmawati; Suardi, Suardi; Habibah, Sitti (UNM (Universitas Negeri Makasar), 2023)
This study aims to determine the results of the implementation of the independent campus learning program in teaching activities, technology adaptation and managerial administrative assistance in partner schools of Gowa Regency. The research approach uses sequential mixed-methods), combining quantitative and qualitative methods. The research location is located at the independent learning partner school of the independent campus of Gowa Regency. The data collection procedure consists of observation, interview, questionnaire and documentation activities. Quantitative data analysis techniques use descriptive statistical techniques measured through Likert scales, while qualitative analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The results showed that the fulfillment of the needs of partner schools in the implementation of the independent campus learning program in the teaching program was in the good category, the technology adaptation program was in the satisfied category and the managerial administrative assistance program was also in the satisfied category. Partner schools are greatly helped by the existence of an independent campus learning program in improving school quality.